2020
DOI: 10.21831/medikora.v19i2.34517
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of kinesio tape toward the ability of legs muscle’s power of amateur basketball players

Abstract: This study aims to find out the effectiveness of kinesio tape use toward legs muscle’s power of amateur basketball players. The method used in this research was quasi experiment method. The population of this research was all of the basketball players. The sample was eleven amateur basketball players that were not competing nationally. Purposive sampling was used as the technique of sample collection. The instruments of this study were test and measurement. The technique of data collection was using survey met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…In a study involving basketball players, it was observed that the vertical jump performance of athletes increased significantly. 24 Aktaş and Baltacı also reported that the increase in isokinetic knee extension peak torque value and jump performance was significant after KT. 25 We think the different results in the literature may be due to factors such as the selected KT technique, the test method used and the population.…”
Section: Discussionmentioning
confidence: 89%
“…In a study involving basketball players, it was observed that the vertical jump performance of athletes increased significantly. 24 Aktaş and Baltacı also reported that the increase in isokinetic knee extension peak torque value and jump performance was significant after KT. 25 We think the different results in the literature may be due to factors such as the selected KT technique, the test method used and the population.…”
Section: Discussionmentioning
confidence: 89%
“…Salah satu hasil penelitian mengatakan bahwa untuk latihan power otot tungkai bawah pada atlet sepakbola dapat diberikan terapi dengan latihan alternate leg boud (Rovendra, 2020). Ada juga penelitian yang membuktikan bahwa dengan kinesio tape mempunyai efek yang signifikan terhadap daya ledak otot tungkai (Lesmana & Nasrulloh, 2020). Sukadiyanto (2009) mengatakan bahwa kecepatan merupakan kemampuan seseorang untuk menjawab rangsangan dalam bentuk gerak atau serangkaian gerak dalam waktu secepat mungkin.…”
Section: Hasil Dan Pembahasanunclassified
“…Increasing the explosive power of the leg muscles can be done by providing an exercise program using either weight training or body weight training (Lesmana & Nasrulloh, 2020). One of the body weight exercises that can be done to train the explosive power of the leg muscles is plyometric exercises.…”
Section: Introductionmentioning
confidence: 99%